2014
DOI: 10.3109/0886022x.2014.900424
|View full text |Cite
|
Sign up to set email alerts
|

The association between renal stone disease and cholesterol gallstones: the easy to believe and not hard to retrieve theory of the metabolic syndrome

Abstract: (2014) The association between renal stone disease and cholesterol gallstones: the easy to believe and not hard to retrieve theory of the metabolic syndrome, Renal Failure, 36:6,[957][958][959][960][961][962] AbstractRenal stone disease and gallstone disease are widely prevalent and costly disease across the globe. Both renal stone disease and gallstone disease are associated with a variety of diseases including obesity, metabolic syndrome, dyslipidemia, hypertension, insulin resistance diabetes and gout. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Several genetic, metabolic and environmental factors for GD and CVD development have been identified. Environmental CVD risk factors include a sedentary lifestyle, a high-fat diet and cigarette smoking, which in turn have all been associated with GD (3,4). Certain lipid metabolizing genes have been identified as susceptibility genes for GD and CVD in genome-wide association studies or meta-analyses (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic, metabolic and environmental factors for GD and CVD development have been identified. Environmental CVD risk factors include a sedentary lifestyle, a high-fat diet and cigarette smoking, which in turn have all been associated with GD (3,4). Certain lipid metabolizing genes have been identified as susceptibility genes for GD and CVD in genome-wide association studies or meta-analyses (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that Huashi Pill significantly increased the water and food intake and enhanced the pH values, which suggested the severity of renal stones was alleviated. In the other hand, the liver function also reflects the digestive function and indirectly affects the formation of renal stones [23]. Therefore, we examined the levels of ALT, AST, and TBIL in the renal rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic liver disease and gallstone disease have previously been shown to be associated with kidney stones. 23 25 The mechanisms linking these diseases with kidney stones are complex and not yet established. In our study, patients with preexisting liver and gall bladder diseases where excluded, and it cannot be ruled out that persisting changes in urinary constituents predispose to liver reactions.…”
Section: Discussionmentioning
confidence: 99%